IMPLEMENTASI EMPLOYEE ASSISTANCE PROGRAM (EAP) DALAM MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN DI PT KANGKUNG MAJU BERSAMA - Damar Wira Pradopo; Edy Kriyanto (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the implementation of the Employee Assistance Program (EAP) at PT Kangkung Maju Bersama, the impact of the Employee Assistance Program (EAP) in increasing employee work productivity at PT Kangkung Maju Bersama, and the challenges and obstacles in implementing the Employee Assistance Program (EAP) at PT Kangkung Maju Bersama. The research method used is descriptive qualitative research. Data collection techniques are more on participant observation, in-depth interviews, and documentation. Data analysis techniques used in this study include data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Implementation of the Employee Assistance Program (EAP) at PT Kangkung Maju Bersama runs with a strategy of practical assistance services and intense psychological counseling socialized to all employees. This program has a significant impact on improving the mental and emotional well-being of employees, which leads to increased productivity through reduced absenteeism, increased focus, loyalty, and teamwork. However, the implementation of the EAP faces challenges such as lack of employee awareness, stigma and concerns about confidentiality, limited counselors, difficult to reach counseling schedules, and a company culture that is not yet fully supportive. Therefore, it is necessary to strengthen outreach, increase resources, and develop a work culture that cares about mental health so that the EAP can more optimally support employees and the company.